Biochemical, Histological, and Multi-Omics Analyses Reveal the Molecular and Metabolic Mechanisms of Cold Stress Response in the Chinese Soft-Shelled Turtle (Pelodiscus sinensis) - Liqin Ji; Qing Shi; Chen Chen; Xiaoli Liu; Junxian Zhu; Xiaoyou Hong; Chengqing Wei; Xinping Zhu; Wei Li (Biology)
The Chinese soft-shelled turtle (Pelodiscus sinensis), a type of warm-water reptile, is frequently chosen as the model animal to understand how organisms respond to environmental stressors. However, the responsive mechanism of P. sinensis to natural cold stress is unclear, especially in terms of metabolic pattern and molecular pathways. Herein, plasma biochemical, hepatic morphological, apoptotic, transcriptomic, and metabolomic detection methods were performed to investigate the response of P. sinensis to acute cold stress. A consistent increase in plasma AST and ALT activities with a decline in ALP activity was found following 14 °C and 7 °C cold stress compared with the control group. Plasma GLU, TG, CHO, and HDL contents, reflecting energy metabolism, were decreased to lower levels from 2 to 16 days post cold stress (dps). Histological and TUNEL detection in the liver demonstrated that the 14 °C and 7 °C cold stress caused severe morphological damage and cell apoptosis in a time-dependent manner. DEGs in the biosynthesis of fatty acids (Acsbg2, Acsl3, Acsl4, Acsl5, Mcat, and Acacb), as well as unsaturated fatty acids (Hsd17b12, Elovl7, Scd, and Baat), starch and sucrose metabolism (Pgm1, Pgm2, and Treh), and apoptosis (Ddit3, Gadd45a, Lmnb1, Tuba1c, Tnf, Tnfsf10, Fos, Itpr1, and Ctso) were discovered in the transcriptome under cold stress. The metabolomic data showed that metabolites, including chenodeoxycholic acid, oleoylethanolamide, uric acid, fructose 1,6-bisphosphate, CMP, and S-(Hydroxymethyl)-glutathione, were remarkably altered in the cold stress groups. Combined transcriptomic and metabolomic data revealed that pyrimidine metabolism, amino acid metabolism, and pyruvate metabolism were the most significant pathways regulated by the low-temperature exposure. Overall, this work suggests that 14 °C and 7 °C cold stress could induce obvious morphological damage and apoptosis in the liver at 4 dps. Moreover, energy metabolism and amino acid metabolism were the main signaling pathways in response to cold stress for P. sinensis.